2022
DOI: 10.18203/2320-1770.ijrcog20220595
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of the vaginal microbiota and its relationship with human papillomavirus

Abstract: The study of bacterial 16S rRNA genes is facilitated with the assistance of next-generation sequencing methods (NGS) which allow a thorough investigation of vaginal microbial community makeup to an extent not achievable with regular culture-supported microbiological methods. The human papillomavirus (HPV) triggers cervical intraepithelial neoplasia (CIN), the precursor of cervical malignancy. Vaginal microbiota has a mutualistic symbiotic connection with their host and has a significant influence on health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Some authors found that the clearance of HPV was delayed among women who had BV, leading to an increasing progression of persistent infection to a precancerous lesion [ 15 ]. Abdalah et al found that patients with established HR-HPV infection had a higher predominance of BV compared to those without infection [ 23 ]. The results of Usyk at al.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found that the clearance of HPV was delayed among women who had BV, leading to an increasing progression of persistent infection to a precancerous lesion [ 15 ]. Abdalah et al found that patients with established HR-HPV infection had a higher predominance of BV compared to those without infection [ 23 ]. The results of Usyk at al.…”
Section: Discussionmentioning
confidence: 99%